PROFIL KLINIS DAN LUARAN PASIEN STROKE-ASSOCIATED PNEUMONIA (SAP) DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Juananda, Desby; Sukiandra, Riki; Maryanti, Yossi; Sucipto, Sucipto; Rahmata Illahi, Annisa; Luo Putra Fau, Joyada; Muslimah Syahrianti, Ukhty (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Introduction: Stroke-associated pneumonia (SAP) is a post-stroke complication that increases morbidity and mortality. Aim: This study aims to examine the clinical characteristics and outcomes to facilitate appropriate clinical decision-making for the treatment and prevention of post-stroke complications. Methods: This cohort retrospective study utilizes medical records of SAP patients at RSUD Arifin Achmad from July 2019 to June 2024. The populations were patients who have developed pneumonia within 48 hours to 7 days after stroke onset. Results: Out of 1,040 stroke patients, 108 (10.4%) developed SAP, with 66.7% classified as definite cases and 33.3% as probable cases. Patients in the ≥60 age group accounted for the highest number of cases (54.6%), with a male-to-female predominance of 64.8%. SAP occurred more frequently in ischemic stroke (68.5%) compared to hemorrhagic stroke (31.5%). Most SAP patients required mechanical ventilation (52.8%). SAP patients required hospitalization, with 45.4% staying for ≤14 days and 53.7% for >14 days. Regarding comorbidities, SAP patients also suffered from hypertension (54.1%), followed by other comorbidities such as diabetes mellitus, chronic obstructive pulmonary disease (COPD), and atrial fibrillation (AF). The blood glucose levels upon hospital admission indicated that SAP patients had a glucose distribution range of 80-144 mg/dl (53.7%), 145-179 mg/dl (14.8%), and ≥180 mg/dl (31.5%). The mortality rate was 57.4%, resulting in 62 deaths. Discussion: This study reveals a significant incidence of SAP in older male stroke patients, especially those with ischemic strokes. The strong association to ventilator use and mortality rates emphasizes the need for early identification and management strategies.